Reaktualisasi Moderasi Beragama bagi Pemuka Agama di Kecamatan Blimbing Kota Malang dalam Membangun Karakter Toleransi dan Moderat - Fannani, Bakhruddin; Ma'arif, A. Samsul; Arifuddin, Nur (Santri : Journal of Student Engagement, 2025)
Religious Moderation as a concept seems to have been accepted maturely, recognized and felt the need by the Religious Leaders of Blimbing District, Malang City. This Community Service Method uses Participatory Action Research (PAR). This assistance uses the PAR (Participatory Action Research) method, a research methodology that invites individuals and communities to actively participate by participating in activities in the same construction or facilities with the knowledge they have. In its implementation there are several stages, namely analyzing problems, preparing program planning, program implementation and program evaluation. Character education can be done early on in the majlis taklim, musholla, mosque and other social organizations. Qualitative studies are carried out with Focus Group Discussions related to the meaning of religious moderation in programs, strategies and implementation in society. The results of this community service show that (1) religious leaders in Blimbing, Malang City agree that religious moderation is important to be encouraged by every Muslim, (2) Religious Moderation is understood as a guide in interacting with fellow religions and between religions, and (3) Among the supporting factors for religious moderation are religious and state instructions and the challenges facing religious moderation are extremist groups and plural societies that require more intensive religious guidance.